Nanotechnology and Immunetherapy: reduction of hepatotoxicity and anti-antineoplastic efficiency: Nanotechnology and Immunetherapy - Araujo-Filho, Irami; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
The integration of nanotechnology and immune therapy presents a revolutionary approach to cancer treatment, merging the precision of nanoscale engineering with the power of the immune system to combat malignancies. This review article explores the synergy between nanotechnology and immune therapy, highlighting its potential to enhance antineoplastic efficiency and mitigate hepatotoxicity, with a particular focus on liver cancer treatments. Nanotechnology offers novel solutions for targeted drug delivery, controlled release, and the co-delivery of therapeutic agents, thus improving the bioavailability and efficacy of immune therapies. By overcoming the challenges posed by the immunosuppressive tumor microenvironment (TME), nanotechnology-enabled strategies can potentiate the antitumor immune response and transform "cold" tumors into "hot" ones, making them more amenable to immune-mediated destruction. Despite promising advancements, the field faces challenges such as optimizing nanoparticle formulations for maximal therapeutic efficacy and safety, identifying suitable targeting ligands for specific cancer types, and addressing the heterogeneity of the TME. Comprehensive preclinical and clinical studies are required to assess the biodistribution, metabolism, and potential toxicity of nanocarriers. This review underscores the transformative potential of combining nanotechnology with immune therapy, offering insights into future directions for more effective, targeted, and safer cancer treatments.